Novel dTDP-l-Rhamnose Synthetic Enzymes (RmlABCD) From Saccharothrix syringae CGMCC 4.1716 for One-Pot Four-Enzyme Synthesis of dTDP-l-Rhamnose - Yang, Shida; An, Xiaonan; Gu, Guofeng; Yan, Zhenxin; Jiang, Xukai; Xu, Li; Xiao, Min (Frontiers in Microbiology, 2021)
Deoxythymidine diphospho-L-rhamnose (dTDP-L-rhamnose) is used by prokaryotic rhamnosyltransferases as the glycosyl donor for the synthesis of rhamnose-containing polysaccharides and compounds that have potential in pharmaceutical development, so its efficient synthesis has attracted much attention. In this study, we successfully cloned four putative dTDP-L-rhamnose synthesis genes Ss-rmlABCD from Saccharothrix syringae CGMCC 4.1716 and expressed them in Escherichia coli. The recombinant enzymes, Ss-RmlA (glucose-1-phosphate thymidylyltransferase), Ss-RmlB (dTDP-D-glucose 4,6-dehydratase), Ss-RmlC (dTDP-4-keto-6-deoxy-glucose 3,5-epimerase), and Ss-RmlD (dTDP-4-keto-rhamnose reductase), were confirmed to catalyze the sequential formation of dTDP-L-rhamnose from deoxythymidine triphosphate (dTTP) and glucose-1-phosphate (Glc-1-P). Ss-RmlA showed maximal enzyme activity at 37 oC and pH 9.0 with 2.5 mM Mg2+, and the Km and kcat values for dTTP and Glc-1-P were 49.56 μM and 5.39 s-1, and 117.30 μM and 3.46 s-1, respectively. Ss-RmlA was promiscuous in the substrate choice and it could use three NTPs (dTTP, dUTP, and UTP) and three sugar-1-Ps (Glc-1-P, GlcNH2-1-P, and GlcN3-1-P) to form nine sugar nucleotides (dTDP-GlcNH2, dTDP-GlcN3, UDP-Glc, UDP-GlcNH2, UDP-GlcN3, dUDP-Glc, dUDP-GlcNH2, and dUDP-GlcN3). Ss-RmlB showed maximal enzyme activity at 50 oC and pH 7.5 with 0.02 mM NAD+, and the Km and kcat values for dTDP-glucose were 98.60 μM and 11.2 s-1, respectively. A one-pot four-enzyme reaction system was developed by simultaneously mixing all of the substrates, reagents, and four enzymes Ss-RmlABCD in one pot for the synthesis of dTDP-L-rhamnose and dUDP-L-rhamnose with the maximal yield of 65% and 46%, respectively, under the optimal conditions. dUDP-L-rhamnose was a novel nucleotide-activated rhamnose reported for the first time.